Alveolar proteinosis and nocardiosis: a patient treated by bronchopulmonary lavage. Issue 767 (September 1989) - Pascual, J.; Gómez Aguinaga, M. A.; Vidal, R.; Maudes, A.; Sureda, A.; Gómez Mampaso, E.; Fogué, L.
Abstract : Alveolar proteinosis is a relatively rare disease of unclear pathogenesis associated with opportunistic-infections. Although nocardiosis is the most frequent one, only 22 cases have been reported previously and are reviewed here. We present a patient with alveolar proteinosis with nocardiosis treated as an emergency with bilateral bronchopulmonary lavage and antibiotics. No previous cases of this association have been successfully managed in this way.